The trouble with transition : no off-the-shelf arrangement for the UK after Brexit - Ondarza, Nicolai von (2017)
Zusammenfassung: The transition will be the most important medium-term issue in the second phase of the Brexit negotiations. The United Kingdom is due to leave the European Union officially in March 2019, too soon to negotiate a detailed agreement on future relations. With neither side standing to gain from a cliff-edge, the British request for a transitional arrangement falls on open ears. But finding agreement will be no easy matter. From the EU’s perspective the only acceptable option is full and complete replication of the status quo, with the UK accepting and implementing EU rules for two years without having any say over them. This will include Prime Minister Theresa May needing to secure a parliamentary majority accepting “rule-taker” status for the UK – and breaking all the promises of the advocates of Brexit for at least two years